Innovation in liposuction cannula to harvest fat graft to use in breast reconstruction - Maurício da Silva Lorena de Oliveira; Elvio Bueno Garcia; Leila Blanes; Christiane Steponavicius Sobral; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The evolution of liposuction and fat graft technique with the oncologic safety allowed to use the fat as autologous filler in patients with breast cancer and submitted to breast reconstruction. The objective is to introduce an innovation in the instrument used to harvest fat grafts for breast reconstruction. Methods: Search of anteriority and trademarks were performed at international and national databases, and a prototype was built as a fat harvest instrument with 35cm in length, 4cm in diameter, with 10 holes at the distal extremity, with 2mm diameter each. It was experimented with a harvest of a viscous substance, comparing the prototype with two regular industry cannulas types: three holes Mercedes’ type and five roles Pitanguy’s type. Results: Four high-relevance patents and one medium-relevance patent were found, which differ from the proposed utility model when comparing the type of design of the distal end of the studied cannulas and the function of the instruments identified. When the prototype’s efficiency was compared with the other cannulas, the cannula with five holes in Pitanguy’s type was the most efficient, and it was no statistical difference between the prototype and the cannula with three roles in Mercedes’ type. Conclusion: The innovation presented to harvest fat graft for breast reconstruction had the same efficiency in harvesting the viscose substance as the cannula Mercedes type with three holes in this experimental model.